Participatory forestry practices and renewable natural resources management (2014)
Despite their importance, the forest resource base in most African countries has continued to dwindle. This continuous decline in Africa forest cover and the inability to stem the tide of deforestation indicate among other things the failure of the classically structured resource management institutions established during colonial administration. Consequently, there has been a paradigm shift in forestry practices throughout the world from the classical management approach to managing the forest in a manner that ensures greater and effective participation of all stakeholders, especially the forest communities. This paper further examines the concept of participatory forestry practices as a model of renewable natural resources management approach. It also discusses the nexus between participatory forestry and sustainable natural resources management, the key steps in establishing participatory forest management, emerging conflicts in participatory forestry practices and avenues for conflict resolution. We contend that for a sustainable participatory forest management, there is need for strong commitment on the part of local people towards maintaining the forest resources through secured forest tenure; upholding a sustainable harvest levels for all the products from the forest; assessing the economic aspects of production and guaranteeing a fair share of the benefits accruing to the local population.